KEBHINNEKAAN BUDAYA SEBAGAI MODAL MERESPONS GLOBALISASI - Heddy Shri Ahimsa-Putra (LITERASI: Indonesian Journal of Humanities, 2014)
There are two important things in Indonesian culture and their relationships to one another, namely the diversity of Indonesian culture and the meaning of cultural diversity for the development of Indonesian culture. In Indonesia cultural diversity is a reality and facts, but also the ideology of nation and state. Therefore, diversity is one of the main characteristics of Indonesian society, both on the outer (physical), and the inner (spiritual). This has a profound impact on the way in which the Indonesians address diversity and difference in everyday life. On the one hand, diversity then takes a form of values that guide the people of Indonesia to address the wide range of diversity and differences, as well as a variety of behavior patterns that are open to it. On the other hand, it manifests itself in a variety of creative culture that is very diverse and hybrid in pattern. In such situations, the authenticity and origins of the elements of foreign culture that come to Indonesia are not considered to be very important. Even more important is the role or the contribution of the various elements of foreign cultures to the development of local and national cultures of Indonesia, as well as for the Indonesian people wherever they are. Keywords: culture, diversity, hybrid, ideology